Rapidly Growing Thyroid Mass in an Immunocompromised Young Male Adult. (9th July 2013) - Santiago, Mónica; Martinez, José Hernán; Palermo, Coromoto; Figueroa, Carlos; Torres, Oberto; Trinidad, Rafael; Gonzalez, Eva; Miranda, Maria de Lourdes; Garcia, Miosotis; Villamarzo, Guillermo
Abstract : We describe a 20-year-old man diagnosed with a myelodysplastic syndrome (MDS), admitted to our hospital due to pancytopenia and fever of undetermined origin after myelosuppression with chemotherapy. Disseminated aspergillosis (DIA) was suspected when he developed skin and lung involvement. A rapidly growing mass was detected on the left neck area, during hospitalization. A thyroid ultrasound reported a 3.7 × 2.5 × 2.9  cm oval heterogeneous structure, suggestive of an abscess versus a hematoma. Fine needle aspiration of the thyroid revealed invasion of aspergillosis. Fungal thyroiditis is a rare occurrence. Thyroid fungal infection is difficult to diagnose; for this reason it is rarely diagnosed antemortem. To our knowledge, this is the 10th case reported in the literature in an adult where the diagnosis of fungal invasion to the thyroid was able to be corroborated antemortem by fine needle aspiration biopsy.